Metamaterial‐based circularly polarised antenna employing ENG‐TL with enhanced bandwidth for WLAN applications. Issue 20 (1st October 2018) - Ameen, M.; Chaudhary, R.K.
Abstract : This work explains the design and development of a low profile and compact single probe‐fed metamaterial (MTM)‐based circularly polarised (CP) antenna using the modified rectangular patch with two pairs of spiral strips and vias for 5.2/5.8 GHz WLAN applications. The intended CP antenna mainly consists of two pairs of radiators and each radiator is realised by using epsilon negative (ENG) transmission line (TL) to generate zeroth‐order resonance. CP characteristics are achieved by placing two radiators for x ‐polarised wave are orthogonally aligned to the other two radiators for y ‐polarised wave. The antenna radiating element offers a compact size of 0.24λ0 × 0.22λ0 with a low profile of 0.04λ0 at 5.5 GHz. To confirm the characteristics of the intended MTM CP antenna design, the designed antenna is fabricated and measured. Measurement results show that the antenna obtains −10 dB impedance bandwidth of 610 MHz (10.86%) which is 2.3 times larger than the standard microstrip patch antenna and axial ratio bandwidth of 140 MHz (2.54%) is obtained.